FORMULATION AND EVALUATION OF GLICLAZIDE NANOSPONGES - SOLUNKE, RAHUL S.; BORGE, UDAY R.; MURTHY, KRISHNA; DESHMUKH, MADHURI T.; SHETE, RAJKUMAR V. (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of the present study was to develop and characterize an optimal stable nanosponges of Gliclazide (GLZ) by using the emulsion solvent diffusion method and aimed to increase its bioavailability and release the drug in sustained and controlled manner. Methods: The GLZ nanosponge was prepared by emulsion solvent diffusion method using different drug-polymer ratios (1:1 to 1:5) Eudragit S100 is used as a polymer. Differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) estimated the compatibility of GLZ with polymer. All formulations evaluated for production yield, entrapment efficiency, in vitro drug release, scanning electron microscopy (SEM) and stability studies. Results: The DSC and FTIR Studies revealed that no interaction between drug and polymer. The Production yield of all batches in the range of 73.8±0.30 to 85.6±0.32. Batch F3 showed the highest production yield, the entrapment efficiency of batch F3 70.6±0.77. The average particle size ranges from 303±2.36 to 680±2.50 nm. By the end of 10th hour F3 formulation shown highest drug release was found to be 94.40±1.12%. The release kinetics of the optimized formulation shows zero-order drug release. The stability study indicates no significant change in the in vitro dissolution profile of optimized formulation. Conclusion: The results of various evaluation parameters, revealed that GLZ nanosponges would be possible alternative delivery systems to conventional formulation to improve its bioavailability, the emulsion solvent diffusion method is best method for preparation of nanosponges and release the drug in sustained and controlled manner.